Dundrennan Abbey: archaeological investigation within the south range of a Cistercian house in Kirkcudbrightshire (Dumfries & Galloway), Scotland - Ewart, Gordon; Carter, Stephen; Crowley, Naomi; Dunn, Andrew; Kenward, Harry; Mills, Coralie; O'Sullivan, Tanya; Radley, Alan; Rankin, Dorothy; Will, Robert; Associates, Geoquest; Connolly, David; et al. (Scottish Archaeological Internet Reports, 2001)
The remains of the south-west corner of the 12th-century Cistercian abbey cloister at Dundrennan (National Grid Reference: NX 7492 4750) were cleared of rubble and 19th-century landscaping infill over four seasons of fieldwork in the early 1990s. Elements of the warming house, novice's day room, great drain and latrine block undercroft were revealed. Coupled with a short programme of geophysical survey and test-trenching, new evidence of the sequence of building for the abbey was revealed by excavation. The project was funded by Historic Scotland.